ETHICAL INFRASTRUCTURE OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV CULTURAL SPACE:CHALLENGES OF IMPLEMENTATION AND FUNCTIONING - Rohozha, Mariya (Ukrainian Cultural Studies, 2023)
The article deals with the ethical infrastructure of Taras Shevchenko Kyiv National University cultural space, the peculiarities of itsimplementation and its functioning due to the challenges facing higher education in Ukraine today. The relevance of studying the ethical provisionof university life is driven by the inevitable value transformations that the university as a cultural institution is experiencing today. By the method ofcase study, the implementation and functioning of the ethical infrastructure at Taras Shevchenko National University of Kyiv is analyzed in the article as a real-time problematic situation. It is shown that the implementation of ethical infrastructure was demanded by the university community and has become a natural process. The thoughtfulness of this process was testified by the thoroughness of preparing the University communitycode of ethics, carrying out the procedures for its discussion and adoption, and preparing the work of the Standing Commission of the Academic Council on Ethics. It also testified to the moral maturity of the university community to comply with the provisions of the code of ethics, to signal violations of its norms and principles, and to seek the truth in the ethical commission. It is about the grassroots (democratic) way of the creation of the code of ethics. And the discussion, comments and proposals from the structural subdivisions are a kind of public examination of the ethical document. The code of ethics, thus adopted by the university community, has become an effective document that sets a coherent system of coordinates in the life of the university. The purpose of the ethical commission is to resolve controversial issues regarding compliance by members of the university community with the code of ethics. Its powers include advising on the usage of the code of ethics and applying its provisions in everyday university life.
Keywords: Taras Shevchenko Kyiv National University; code of ethics; ethical commission; ethical infrastructure; cultural space